PENGARUH EKSTRAK DAUN KELOR TERFERMENTASI MELALUI AIR MINUM TERHADAP PERSENTASE EKSTERNAL OFFAL BROILER - Ansyarullah, J.,; I K. Sumadi.,; G. A. M. K. Dewi (Jurnal Peternakan Tropika, 2025)
The utilization of fermented moringa leaf extract as a natural feed additive is due to theprohibition of the use of Antibiotic Growth Promoter (AGP) due to the resistance effect caused in broilers. This study aims to determine the effect of giving fermented moringa leaf extractthrough drinking water on the external offal percentage of broiler carried out at Farm Sesetan,Faculty of Animal Husbandry, Udayana University in 4 weeks. Completely RandomizedDesign (CRD) was used in this study with 3 treatments, 6 replicates and each consisting of 5broilers. The treatments were broilers given drinking water without moringa extract(EF0/control), broilers given drinking water with 3% fermented moringa extract (EF1), andbroilers given 6% fermented moringa extract in drinking water (EF2). The variable observedwas the percentage of broiler external offal including (percentage of blood, percentage offeathers, percentage of head, percentage of neck and percentage of feet). The results indicatedthat there was no significant difference (P>0.05) in the percentage of external broiler offal(percentage of blood, percentage of fur, percentage of head, percentage of neck and percentageof feet) compared to the control (EF0). Based on the results of this study, it was concluded thatthe administration of fermented Moringa leaf extract as much as 3% and 6% in drinking waterdid not affect the external ofal percentage of broiler. ABSTRAK Pemanfaatan ekstrak daun kelor terfermentasi sebagai feed additif alami dikarenakanadanya pelarangan penggunaan Antibiotic Growth Promoter (AGP) akibat efek resistensi yangditimbulkan pada broiler. Penelitian ini memiliki tujuan untuk mengetahui pengaruh pemberianekstrak daun kelor terfermentasi melalui air minum terhadap persentase eksternal offal broileryang dilaksanakan pada Farm Sesetan, Fakultas Peternakan, Universitas Udayana dalam 4minggu. Rancangan Acak Lengkap digunakan dalam penelitian ini (RAL) dengan 3 perlakuan,6 ulangan serta tiap-tiapnya terdiri dari 5 ekor broiler. Perlakuan diberikan yaitu broiler yangdiberikan air minum tanpa ekstrak daun kelor (EF0/kontrol), broiler yang diberikan air minumdengan 3% ekstrak daun kelor terfermentasi (EF1), serta broiler yang diberikan 6% ekstrakdaun kelor terfermentasi dalam air minum (EF2). Variabel yang diamati adalah persentaseeksternal offal broiler meliputi (persentase darah, persentase bulu, persentase kepala, persentaseleher dan persentase kaki). Hasil penelitian mengindikasikan tidak terdapat perbedaan yangsignifikan (P>0,05) atas persentase eksternal offal broiler ialah (persentase darah, persentasebulu, persentase kepala, persentase leher dan persentase kaki) dibandingkan kontrol (EF0).Berdasarkan hasil penelitian disimpulkan bahwa pemberian ekstrak daun kelor terfermentasisebanyak 3% dan 6% dalam air minum tidak memberikan pengaruh terhadap persentaseeksternal offal broiler.